Problemas fitosanitarios que amenazan la conservación de las orquídeas de Costa Rica - Rivera-Coto, German (Universidad de Costa Rica, 2015)
Orchids from private collections, nurseries and wild areas, located in different ecological regions of Costa Rica, were studied in order to know the pests and diseases affecting them. 16 insect and two mite genera were identified as pests on different orchids and 28 pathogens were found as causal agents of infec- tious diseases. The most frequent pests were: Tenthecoris orchidearum, Stethobaris sp., Xylosandrus com- pactus, Pseudococcus longispinus, Diaspis boisduvalii and Tenuipalpus pacificus. The main diseases found were caused by: Phytophthora spp., Pythium spp., Fusariun oxysporum, Fusarium spp., Sclerotium rolfsii, Colletotrichum gloeosporioides, Sphenospora spp., Uredo spp., Cymbidium Mosaic virus and Odontoglossum Ring Spot Virus. This results demonstrate the diversity of organisms producing sanitary problems on orchids in Costa Rica, and suggests the inclusion of pest and diseases management in strate- gies for orchid conservation.